Mekanisme Kemitraan dalam Pengendalian Kejahatan Lintas Negara (Analisis Kasus Korupsi Alstom oleh Komisi Pemberantasan Korupsi) - Sari Wardhani Ismakoen (Universitas Budi Luhur, 2023)
Organized crime today is a pressing concern in every country, whether as a supply, transit, or victim country. Criminal networks have spread all over the world and cross borders, so efforts to combat transnational crime must also use cross-border cooperation to ensure that organized crime networks do not simply divert their activities to countries or regions where cooperation is weak as a reflection of the weak criminal justice response. Corruption is a transnational crime. The results of corruption are often hidden by criminals with mechanisms that make law enforcement efforts and efforts to return assets against state losses not optimal. This is similar to corruption cases in Indonesia which use cross-jurisdictional affiliations to obscure traces of corruption acquisition. Law enforcement officials face many obstacles and problems in handling issues to trace the flow of criminal funds (follow the money) and track perpetrators (follow the suspect) records when criminal offenders are affiliated with criminal offenders across Indonesian or foreign jurisdictions. Therefore, cooperation in handling transnational crimes is one of the conditions for successfully resolving corruption cases. The implementation of cooperation is adapting to the strategic focus of each institution, which can be in the form of investigation, law enforcement, prevention, awareness, and education, or a combination of several elements or as an entire. The pattern of cooperation can be in the form of networking, coordinating, cooperating, and collaborating. Analyzing the Alstom case handled by the KPK provides a practical example of an inter-agency counter-crime cooperation strategy to tackle corruption and recover state assets.